A paternidade na UTI neonatal: o pai prematuro - Maria de Lourdes de Melo Baeta (2009)
This study proposes looking into the participation of father in caring for their premature babies in the neonatal ICU, as well as the influences of that environment in their relationships, according to their own perspectives and under theoretical presuppositions of psychoanalysis. Fathers were interviewed in situ, using qualitative research methods, while their children were in the NICU. On the whole, the Institution treats patients who have a Medical Insurance Plans and who have been referred by hospitals from Belo Horizonte and from other Brazilian cities. Ten fathers were interviewed under the Saturation Sampling Criteria (FONTANELLA, RICAS, TURATO, 2008) during July and August 2008. It is very relevant to mention at this point that their interviews can be interpreted by a psychoanalytical approach since they have been transcribed by the researcher literally. Data were analyzed accordingto a psychoanalytical based methodology that has been proposed by Pinto (2001). From such analysis were identified the Convergence Themes by means a symbolic reduction. One theme was avoided by fathers as it was close to a traumatic situation, that is, premature birth and sudden interruption of mothers pregnancy that caused own parenting roles to be discontinued. This discontinuity caused tension on fathers between mother´s push and the confirmation of the sexual role required by castration. This is what we mean by premature father. The confirmation of the sexual role opposed to what is not feminine by nature but the mothers imaginary falo, where no sexuality matters , has made fathers find their places back in regards to giving support to their wives by making a distinction between woman and mother ,element of desire support between a couple. Another convergence element has been sharing fatherhood in the NICU, to what we have named medicine-partner, and the transference relationships that have been established with it. Bearing all that in mind, we conclude that even though the baby is a real patient, the Neonatal environment isin fact a place where families begin developing their first relationships in life even if there are medical issues in between. These medical issues are as necessary as the family ones and even though they are distinct from one another, they end up weaving. Transference is the mechanism parents use to cope with medical impersonal issues by making them more personal. We feel it is relevant to mention the fact that it is not possible to ignore the scope of transference in relation to the medicine-partner and to the possible work on symbolic, imaginary and real dimensions present in the whole situation. We propose the health professional to promote intentionally the fathers involvement in the child medical treatment. By doing so, fathers will perform the role proposed by themselves and symbolic transference will minimize the undesirable effects of both imaginary and real threats. However, we are aware of the fact that places in the structure are vacant until each man occupies his own spot according to his own personal ways. Transference handling will be easier to some but those who find the process harder may be greatlyhelped by psychologists that will be able to assist them according to their particular needs.